Improvement in quality of life after catheter ablation for paroxysmal versus long-standing persistent atrial fibrillation: a prospective study with 3-year follow-up - Bulková, Veronika; Fiala, Martin; Havránek, Stěpán; Simek, Jan; Skňouřil, Libor; Januška, Jaroslav; Spinar, Jindřich; Wichterle, Dan (Journal of the American Heart Association, 2014)
BACKGROUND: Changes in quality of life (QoL) after catheter ablation for long-standing persistent atrial fibrillation (LSPAF) are not well described. We sought to compare QoL improvement after catheter ablation of paroxysmal atrial fibrillation (PAF) versus that after LSPAF. METHODS AND RESULTS: A total of 261 PAF and 126 LSPAF ablation recipients were prospectively followed for arrhythmia recurrence, QoL, hospital stay, and sick leave. In PAF versus LSPAF groups, 1.3±0.6 versus 1.6±0.7 procedures were performed per patient (P<0.00001) during a 3-year follow-up. Good arrhythmia control was achieved in 86% versus 87% of patients (P=0.69) and in 69% versus 69% of patients not receiving antiarrhythmic drugs (P=0.99). The baseline QoL was better in the PAF than in the LSPAF group (European Quality of Life Group instrument self-report questionnaire visual analog scale: 66.4±14.2 versus 61.0±14.2, P=0.0005; European Quality of Life Group 3-level, 5-dimensional descriptive system: 71.4±9.2 versus 67.7±13.8, P=0.002). Postablation 3-year increase in QoL was significant in both groups (all P<0.00001) and significantly lower in PAF versus LSPAF patients (visual analog scale: +5.0±14.5 versus +10.2±12.8, P=0.001; descriptive system: +5.9±14.3 versus +9.3±13.9, P=0.03). In multivariate analysis, LSPAF, less advanced age, shorter history of AF and good arrhythmia control were consistently associated with postablation 3-year improvement in QoL. Days of hospital stay for cardiovascular reasons and days on sick leave per patient/year were significantly reduced in both groups. CONCLUSIONS: Patients with LSPAF had worse baseline QoL. The magnitude of QoL improvement after ablation of LSPAF was significantly greater compared with after ablation of PAF, particularly when good arrhythmia control was achieved without the use of antiarrhythmic drugs.
Keywords: dospělí; Recurrence; Female; Atrial Fibrillation; Quality of Life; úzkost; Adult; výsledek terapie; ženské pohlaví; mladý dospělý; Catheter Ablation; kvalita života; lidé; Activities of Daily Living; recidiva; katetrizační ablace; Treatment Outcome; následné studie; Anxiety; hospitalizace; kohortové studie; Cohort Studies; činnosti denního života; prospektivní studie; Follow-Up Studies; Male; Aged; Prospective Studies; Sick Leave; Hospitalization; Young Adult; fibrilace síní; deprese; lidé středního věku; senioři; mužské pohlaví; Depression; Middle Aged; pracovní neschopnost; Humans